Adverse Influence of Mixed Acidemia on the Biocompatibility of Continuous Veno‐Venous Hemofiltration With Respect to the Lungs. Issue 12 (5th June 2013) - Wagner, Johanna‐Josophina; Bedarf, Janis R.; Russ, Martin; Grosch‐Ott, Sascha; Keckel, Tobias; Hiebl, Bernhard; Schell, Hanna; Unger, Juliane K.
Abstract Experimental data indicate that hypercapnic adidosis has anti‐inflammatory effects. These anti‐inflammatory effects may even be a beneficial property in case of low tidal volume ventilation with consecutive hypercapnic acidosis. It is unclear whether these anti‐inflammatory effects predominate in critically ill patients who suffer from multiple pro‐ and anti‐inflammatory insults like extracorporeal organ support (pro‐inflammatory), metabolic acidosis (pro‐ and anti‐inflammatory), as well as hypoxia (pro‐inflammatory). Eighteen pigs were randomized into three groups, mechanically ventilated and connected to a continuous veno‐venous hemofiltration (CVVH) as pro‐inflammatory insult. A reference group with normal acid‐base state obtained normoventilation; a normoxemic acidemia group obtained normoxemic, mixed acidemia due to infusion of lactic and hyperchloremic acid and low tidal volume ventilation, and in a hypoxemic acidemia group the mixed acidemia was paralleled by hypoxemia. Lung histology including pulmonary leukocyte invasion, blood gases, blood cell counts, and hemodynamics were examined. The histological examination of the lungs of acidemic pigs showed a suppressed invasion of leukocytes and thinner alveolar walls compared with normoventilated and with hypoxemic pigs. Enhanced congestion and alveolar red blood cells (RBCs) combined with an increase of the pulmonary artery pressure were observed in acidemic pigs in comparison with the reference group. Normoxemic acidemia reduced the pro‐inflammatory reaction to the CVVH and mechanical ventilation in the ventilated lung areas in the form of pulmonary leukocyte invasion. However, this did not result in reduced scores for lung injury. Instead, an increased score for criteria which represent lung injury (congestion and alveolar RBCs) was observed in acidemic pigs.